Legend and History in Works by George Lippard - N. A. Tulyakova (Научный диалог)
The historical works by George Lippard “Legends of revolution” and “Legends of Mexico” are analyzed. The aim is to identify genre features of historical prose of Lippard in the context of trends of the era. The comparative analysis of the works of Lippard and invariant of the genre of the historical novel of the first half of the 19th century is made. The features of the narrative organization, narrative structure, system of characters, art-time in the works by Lippard are discussed. It is proved that Lippard draws the narrative that differs from the canon of the historical novel, but correspond with his genre definition of the legend. It is demonstrated that Lippard robs the narrative of suspense and pays special attention to allusions to biblical events and open mapping the historical figures with characters of sacred history. It is shown that the main events in the history of Lippard are betrayal and revenge for him, and almost all the characters set before a choice between loyalty and treason determining the course of earthly and divine history; in recent American history, such events are the War for Independence and the Civil war. It is concluded that the historical narrative of Lippard is significantly different from the traditional historical novels of the 19th century.